Utiliization of Natural Compound from Pegagan (Centella asiatica (L.) Urb.) and Their Potential Role in the Health Sector - Ratna Lestyana Dewi; Ratna Yuniati; Yasman (Postgraduate, University of Mataram, 2025)
Centella asiatica, also known as Gotu Kola, is a medicinal plant widely used in traditional medicine. This abstract discusses its various health benefits supported by scientific research, including wound healing, cognitive enhancement, and anxiety reduction. It also explores its potential in treating skin conditions, venous insufficiency, and improving circulation. Further research is needed to fully understand its mechanisms of action and optimize its therapeutic applications. Centella asiatica (C. asiatica), commonly known as Gotu Kola, is a herbaceous plant extensively used in traditional Asian medicine for centuries. This review summarizes the scientifically validated health benefits of C. asiatica based on available research, primarily from Scopus-indexed publications. The plant's bioactive compounds, including triterpenoid saponins (asiaticoside, madecassoside, asiatic acid, and madecassic acid), contribute to its diverse pharmacological activities. C. asiatica exhibits significant wound healing properties by promoting collagen synthesis, angiogenesis, and fibroblast proliferation. Furthermore, studies suggest its potential in enhancing cognitive function, reducing anxiety, and improving memory. Its efficacy in treating skin conditions like eczema and psoriasis, as well as venous insufficiency and microcirculation, has also been reported. While promising, further research is needed to elucidate the precise mechanisms of action, determine optimal dosages, and explore potential synergistic effects with other therapeutic agents for various health conditions. This review aims to provide a comprehensive overview of the evidence-based health benefits of C. asiatica, highlighting its potential as a valuable natural remedy in modern medicine.